Impact of metabolic enzyme activity variability on dabrafenib disposition - Wang, Shi-yu; Chen, Qing; Chen, Zhong-xi; Chen, Jing; Yuan, Jing; Dai, Li-shang; Chen, Lian-guo; Zhang, Xiao-dan (Frontiers in Pharmacology, 2025)
IntroductionThe systemic exposure of dabrafenib correlates with its adverse drug reactions. A thorough understanding of its pharmacokinetic profile is crucial for precise clinical application.MethodsAn optimized liver microsomal incubation system was established to screen for inhibitors of dabrafenib metabolism. Recombinant human CYP3A4 microsomes were prepared using a baculovirus-insect cell expression system. Analytes were quantified using ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS). The in vivo relevance of the inhibitory effects was further validated in Sprague-Dawley rats.ResultsLoratadine was identified as the most potent inhibitor, with IC50 values of 14.01 ± 2.82 μM in rat liver microsomes and 52.40 ± 4.63 μM in human liver microsomes. It suppressed over 90% of dabrafenib metabolism through mixed-type inhibition. In vivo, co-administration of loratadine significantly increased the systemic exposure of dabrafenib compared to administration of dabrafenib alone. Specifically, the half-life (T1/2) and peak concentration (Cmax) increased by 548.65% and 237.43%, respectively, while CLZ/F and VZ/F were markedly reduced. These effects were attributed to inhibition mediated by loratadine. Additionally, CYP3A4 genetic polymorphisms considerably influenced the pharmacokinetics of dabrafenib: the CYP3A4.28 variant exhibited higher intrinsic clearance than the wild-type CYP3A4.1, whereas CYP3A4.8 showed reduced clearance.DiscussionBoth loratadine-mediated drug-drug interactions and CYP3A4 genetic polymorphisms critically alter the metabolism of dabrafenib. Dosage adjustments are necessary when these factors are present concurrently.